Vibration control of a very flexible manipulator system - Mohamed, Zaharuddin; Martins, Jorge M.; Tokhi, Mohammad Osman; SaÌ? da Costa, JoseÌ? M G S; Botto, Miguel Ayala (Elsevier B.V., 2005)
This paper presents experimental investigations into the development of feedforward and feedback control schemes for vibration control of a very flexible and high-friction manipulator system. A feedforward control scheme based on input shaping and low-pass filtering techniques and a strain feedback control scheme are examined. To study the effectiveness of the controllers, initially a collocated PD control is developed for control of rigid body motion. The performances of the controllers are assessed in terms of the input tracking capability and vibration reduction as compared to the response with PD control. Moreover, the robustness of the feedforward control schemes is discussed. Finally, a comparative assessment of the control strategies is presented.